(3eTGQb GdCfhGQ GdfHhjI ef UMGM GdCNHGQ GdeUWahjIs - (3GdMSf Hf eMeO Hf GdMSf Hf MjOQ GdYOhj GdYeQj GdUGZGfj GdMfaj QVqj GdOjf,J (B650 (3g` s ((3CUagGf s)
(3ChdgG (B:s
(3GdMeO ddg eMi GdQee CeG HYO aEfi ePJOQLJ eQGbi GdTQa hdeG JhLfi Gddg JYGdi hOhLfi HJGL eUHGM GdOLi ef UMGM MOjK GdeUWai hSejJg eTGQb GdCfhGQ GdfHhjI s
(3BNQgG (B:s
(3e CfS dHjc YeQI hMLLkG Je cJGH eTGQb GdCfhGQ s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B162s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fbdJ Yf fSNI efbhdI Yf CUd Jdi Ydi GdeDda hcJH ai BNQg HNWg s
(3cJHJ GdQehR HGdRQbI hGdMeQI hGdePgH s
(3Ydi GdfSNI JbjjOGJ cKjQI s
(3HBNQgG bQGAI GdfGSN Ydi SjO GdeMOKjf YRjR GdedI hGdOjf GdMSf GdQLGFi SfI (B770 (3g` HOGQ GdMOjK HCUagGf s
Keywords: (3GdMOjK h GdeUWdMs